Adobe Photoshop - Laskevitch, Stephen (Rocky Nook, 2020)
Adobe Photoshop: A Complete Course and Compendium of Features is your guide to creating, editing, and enhancing images and designs in Adobe Photoshop. Whether you're retouching a photograph, making a simulated chalk drawing, or creating a composite photo with a 3D drawing, Photoshop is the tool for you-and this book will teach you what you need to know. First, with a complete Course that includes a set of projects and lessons derived from Adobe Certified Instructor Steve Laskevitch, you will learn the procedures needed to use Photoshop effectively and professionally. Dozens of lessons are included that can be applied to any graphics you have in mind. Through these step-by-step lessons, you'll be exposed to all of Photoshop's features in practical contexts and its best practices for optimal workflows. To complete the Course, we'll supply lesson documents and their assets to download. These can even serve as starting points for your own projects. Then, for greater depth of knowledge and subsequent reference, you'll use the Compendium to uncover more of the "how" and "why" of Photoshop. With each topic easy to access, you can find and explore all of Photoshop's key features and concepts in depth. With cross references between the Course and Compendium, the two parts of the book complement each other perfectly. Best of all, when the lessons in the Course are done, the Compendium will continue to serve for months and years to come. Learn step by step how to: • Set up an ideal workspace • Master selections and masks • Work with type and brushes • Use blend modes for combining images • Take advantage of Smart Objects • Become more efficient and effective with actions and scripts • And much more!